The Assessment on Reading Comprehension at SMAN 22 Makassar - Adi Nugraha; Baso Jabu; Haryanto Atmowardoyo (Celebes Journal of Language Studies, 2021)
Assessment in reading comprehension is very important for students to know their ability. Using the right assessment can affect the development of the students reading comprehension. This research aims at finding out the type of assessment that teachers use, why teachers prefer to use the current assessment, and the teacher preparation, implementation, and score the students reading comprehension. The data were taken through interviews and observation. The subject of the research was the teacher of SMAN 22 Makassar. The result of this research: The type of assessment used by teachers at SMAN 22 in assessing reading comprehension is formative assessment. In the assessment aspect of reading comprehension, not all aspects are taken by the teacher in assessing students' reading comprehension, only a few aspects, namely main idea, supporting detail and vocabulary, and likewise, the components in reading comprehension, only a few are taken by the teacher, namely vocabulary, fluency, and comprehension. In using the assessment to assess the students' reading comprehension, the teacher also adjusts to the KD given to the teacher. With this KD the teacher will adjust what assessment should be used and also in each test the teacher gives students so that they know the progress of their reading comprehension will be adjusted to the abilities of the students. The teacher always prepares whatever is needed in teaching reading comprehension. In each lesson, the teacher implements the teaching from the lesson plan and give score to the students based on the result of the answers in the given task format.